Implementasi Digital Marketing pada “Usaha Es Teh Rindu” - Irfan Ariyanto; Rini Arvika Sari (ABDIMAS TERAPAN : Jurnal Pengabdian Kepada Masyarakat Terapan, 2025)
This community service project aims to implement a digital marketing strategy for Es Teh Rindu, a micro, small, and medium enterprise (MSME) specializing in natural tea-based beverages. The methods applied include SWOT analysis, the marketing mix (4Ps), and the STP (Segmentation, Targeting,Positioning) approach. The digital marketing strategy was implemented through the creation of a Google My Business account, the use of social media platforms (Instagram and Facebook), the development of a content calendar, and the creation and publication of promotional content for one month. The results showed increased audience engagement based on social media insights, improved brand awareness, and growing interest from consumers outside the local area. The analysis also highlights that consistent and informative content strategies can build consumer trust and significantly expand market reach. Challenges such as limited digital literacy were addressed through training and direct mentoring. This project not only supports the digital transformation of Es Teh Rindu but also provides practical insights for other MSMEs seeking to adopt digital marketing as a business development strategy. Therefore, this activity contributes to the government’s program to accelerate the digitalization of MSMEs in Indonesia.